Traffic noise mapping of Indian roads through smartphone user community participation - Kumar, R.; Mukherjee, Abhijit; Singh, V. (Springer Netherlands, 2017)
Road traffic noise pollution is a global hazard, and rapid urbanization has aggravated the problem. This paper explores a novel approach which involves a smartphone user community to monitor the prevalent noise. The system involves a client application on smartphones that records noise, processes the information and communicates to a server and shares the information as visual noise levels on Google® Maps. A fuzzy logic-based classification of noise is proposed. Results from residential, commercial, and industrial areas of the northern region of India are demonstrated. The noise levels are generally found to be higher than the prescribed standards. The experiment demonstrates the huge potential of user community participation in monitoring noise pollution.